Structure of electron fluxes emitted from cathode flares in the initial stage of a vacuum breakdown; Russian Physics Journal; Vol. 13, № 8 - Bakhenov i. e. [Bazhenov] G. P. (1970, 1970)
В фонде НТБ ТПУ отсутствует